Spanish at Work - Lorenzo-Dus, Nuria. author. aut Link
XIII, 292 p.
Keywords: A state-of-the-art collection of works on institutional discourse across the Spanish-speaking world. This volume focuses on how language is used in the media, politics and the workplace; what discursive identities are constructed; and how interpersonal relations are negotiated.